Organic Phase Change Materials And Their Textile Applications: An Overview - Önder, Emel; SARIER, NİHAL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2012)
An organic phase change material (PCM) possesses the ability to absorb and release large quantity of latent heat during a phase change process over a certain temperature range. The use of PCMs in energy storage and thermal insulation has been tested scientifically and industrially in many applications. The broad based research and development studies concentrating on the characteristics of known organic PCMs and new materials as PCM candidates, the storage methods of PCMs, as well as the resolution of specific phase change problems, such as low thermal conductivity and supercooling have been reviewed. The potential industrial applications of PCMs in textiles and clothing systems, the methods of PCM integration into textiles and the methods of evaluating their thermal properties are also presented in this study. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: PCM; Dynamic Heat Storage; Textile; Microencapsulation; Thermal Conductivity; Supercooling; Thermal-Energy Storage; Latent-Heat Storage; Change Materials Pcms; Differential Scanning Calorimetry; Microencapsulated n-octadecane; Fatty-acid Esters; Poly(ethylene oxide) Fractions; High-Density Polyethylene; In-Situ Polymerization; Shape-Stabilized Pcm; Dinamik Isı Depolama; Tekstil; Mikrokapsülleme; Termal İletkenlik; Aşırı Soğuma; Termal Enerji Depolama; Latent Isı Depolama; Değişim Materyalleri; Diferansiyel Tarama Kalorimetrisi; Mikrokapsüllü n-oktadekan; Yağ Asidi Esterleri; Poli (etilen oksit) Kısımlar; Yüksek Yoğunluklu Polietilen; İn-situ Polimerizasyon